The Influence of Halal Labeling and Product Quality on Intention to Purchase Azarina Hydrasoothe Sunscreen - Rini, Ika Tirta Candra; Hartadi, Agung; Budiningrum, Endah Wening (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This study aims to determine the effect of halal labeling and product quality on buying intention of Azarine Hydrosoothe Sunscreen. This research approach uses quantitative research .The research was conducted in March. The number samples in the study were 109 respondents using the accidental sampling technique. Then analyse the data obtained in the from of quantitativ e analysis which includes descrptive analysis, validity test, reliability test, hypothesis testing through t test. Test the analysis of the coefficient of determinan (R2) classical assumption test and multiple linier regression analysis which serves to see the influence between variables. The results of this study indicate that halal labeling and product quality have an effect on purchas intention. Correlation coefficeient (R) value is 0,830 which indicates a strong and positifve relationship. While the coefficient of determinan (adjusted R2) is 0, 682. This shows that 0,682 or 68,2% of purchase intention is influenced by the independet variables, namely halal labeling and product quality, while the remaining 31,8% is influenced by order variables not examined in this study